Implementasi Modul Ajar di Sekolah SMP N 12 Palangka Raya dalam Mata Pelajaran PAK Kelas VII SMP - Martesa Martesa; Jesika Sabatini Ayakeding; Luis Fernando; Matius Timan Herdi Ginting (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study aims to describe the implementation of the Christian Religious Education teaching module on the topic "Gratitude for God's Creation" in grade VII of SMP Negeri 12 Palangka Raya. The implementation was carried out to help students understand the meaning of gratitude for God's creation and apply it in everyday life through active and creative learning activities. The learning activities used group discussion methods, faith projects, role-playing, presentations, and personal reflection so that students were directly involved in learning, not only as listeners but as active actors in the learning process. The research subjects were three students who participated in the learning according to the Christian Religious Education subject schedule. The results showed that students were able to recognize and name various creations of God through reading Genesis 1:1–31, express gratitude through poster works and simple songs, and show enthusiasm during the learning process. The assessment of learning outcomes showed that two students obtained the good category and one student the adequate category, which means that the implementation of this teaching module has a positive impact on the development of students' knowledge, attitudes, and skills.